P25 SUBCUTANEOUS–ICD IN PATIENTS WITH HEART FAILURE: RESULTS FROM A MULTICENTER, EUROPEAN ANALYSIS. (18th May 2022) - Schiavone, M; Gasperetti, A; Mitacchione, G; Angeletti, A; Vogler, J; Laredo, M; Breitenstein, A; Gulletta, S; Fastenrath, F; Kaiser, L; Compagnucci, P; Palmisano, P; et al.
Abstract: Background: Data on patients with heart failure (HF) with a subcutaneous implantable cardioverter defibrillator (S–ICD) are scarce. Objective: Aim of this study was to assess clinical outcomes of the S–ICD in HF patients in a real–world analysis from the largest European retrospective S–ICD registry (ELISIR). Methods: All consecutive patients undergoing S–ICD implantation at several European institutions were used for the current analysis. The population was classified into two groups: the HF (classified as HF with reduced and mid–range ejection fraction – HFrEF and HFmrEF) vs the no–HF cohort. The primary outcome of the study was the inappropriate shock (IS) rate across the two cohorts. As secondary outcomes, appropriate shocks, cardiovascular mortality and device–related complications during follow–up were assessed Results: A total of 1409 patients from the ELISIR registry were included; HF patients represented 57.3% of the entire cohort (n = 701, 86.9% HFrEF; n = 106, 13.1% HFmrEF). Over a median follow–up of approximately 2 years, a total of 133 inappropriate shocks were observed in the entire cohort, without significant differences among the two groups (9.2% vs 9.8%, p = 0.689). 133 complex ventricular arrhythmias were adequately recognized and treated, with similar rates of appropriate shocks (9.2% vs 9.8%, p = 0.689). Inappropriate and effective shocks–free survival has been represented in Figure 1 (Kaplan–Meier estimates). At multivariate analysis (Figure 2), age (HR = 0.974 [0.955–0.992], p = 0.005), LVEF (HR = 0.954 [0.926–0.984], p = 0.003), arrhythmogenic right ventricular cardiomyopathy – ARVC (HR = 3.364 [1.206–9.384], p = 0.020) and smart pass + (HR = 0.321 [0.184–0.560], p < 0.001) remained associated with inappropriate shocks. Moreover, a low number of patients (n = 76) experienced device–related complications, more frequently in the HF cohort (6.2% vs 3.8%, p = 0.031) with no significant differences regarding any specific outcome of interest: lead infection (1.1% vs 0.7%, p = 0.381), pocket infection (1.9% vs 0.8%, p = 0.107), pocket hematoma (3.2% vs 2.8%, p = 0.668). Conclusion: The use of S–ICD in HF patients did not result in a higher rate of inappropriate shocks when compared to no–HF patients, even when stratifying for LVEF. Only age, LVEF, ARVC e Smart Pass algorithm were predictors of the primary outcome at multivariate analysis. Despite a lower overall rate of complications in the entire cohort, HF patients experienced device–related complications more frequently.